The Level of Burnout Among Palestinian Media Professionals in the West Bank, Palestine - Dweekat, Ahmed Hussein Abdel Rahman; Al-Arja, Naheda Saba Naji (Journal of Posthumanism, 2025)
This study aims to identify the level of burnout among Palestinian media professionals in West Bank. It also aims to focus on the role of different factors such as gender, experience, and academic qualifications on their level of burnout.The Methodology of this study: A descriptive analytical approach was used, using the Burnout Scale as a study tool. The study sample consisted of (182) Palestinian media professionals in the West Bank, selected using a stratified random sampling method.Results: The results showed an average response to the main question. Average scores were recorded in all areas, with the highest score in ​​promotion and development, and the lowest score in the area of ​​anger management. Furthermore, there were no statistically significant differences attributable to gender and qualifications, while there were statistically significant differences attributable to the experience variable in favor of the age group (11-15 years).Conclusion: Despite the importance of burnout, there are insufficient studies in Palestine. This study emphasizes the need to provide journalists with information about the concept of burnout, its causes, sources, and how to deal with it. The results indicate the need to provide psychological counseling to media professionals to treat its symptoms and disorders.